Establishing the Links between Online Activity and Car Use: Evidence from a Combined Travel Diary and Online-Activity Pseudodiary Data Set. Issue 1 (January 2014) - Le Vine, Scott; Latinopoulos, Charilaos; Polak, John
The links between online activity and physical mobility are of wide and growing interest to researchers, practitioners, and policy makers. This paper presents the results of an analysis of microdata from the Scottish household survey. The survey provides a unique, large-scale, nationally representative data set that includes both a travel diary instrument and a pseudodiary of participation in online activity. Multivariate regression models were estimated to relate people's online-activity pro-files with their car driving mileage. The models included demographic and spatial characteristics to control for potential confounding effects. The analysis found that, net of other effects, compared with nonuse of the Internet, Internet usage was associated with a higher level of car use. The marginal effect of time spent online was, however, found to be negatively linked with car use. In other words, spending large amounts of time online is, all else equal, associated with less car driving mileage. The paper concludes with a discussion of further research needs to advance this line of inquiry.